Central Pontine Myelinolysis Secondary to Hyperglycemia: A Case Report - Moussa, Walid Mohamed; OUALI, Ibtissam EL; MOUSSA, Aicha HOUSSEIN; DENDANE, Tarek; ZEGGWAGH, Amine Ali (RA Journal of Applied Research, 2023)
Centropontine myelinolysis (MCP) belongs to the osmotic demyelination syndrome, and occurs especially after the rapid correction of hyponatremia. In rare cases, it is caused by states of hyperosmolarity and it can be seen in hyperglycemia. Here, we report the case of a 32-year-old diabetic patient, admitted to intensive care unit for a disorder of consciousness and seizures. The physical examination found an apyretic patient with, Glasgow at 11, with quadriparesis and high blood pressure. Laboratory investigations showed hyperglycemia and metabolic ketoacidosis with chronic renal failure, natremia was normal, lumbar puncture was also normal. The diagnosis of MCP was retained on the MRI. Insulin therapy and rehydration were started and the patient showed a clinical improvement. However, he died because of ventilator-associated pneumonia. The aim of this work is to show that MCP can occur in the absence of an abnormality of natremia and this diagnosis should be considered in diabetic patients with neurological disorders.